Factors Influencing Mothers' Decisions to Choose Implant Contraception - Nur Andriani Tanu; Nila Widya Keswara (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
The choice of implant contraception is an important decision in reproductive health because it relates to the effectiveness of pregnancy prevention, the sustainability of contraceptive use, and women's autonomy. Although implants are a highly effective long-term contraceptive method, their use in Indonesia is still relatively low and is influenced by various individual and social factors. This study aims to analyze the factors that influence mothers' decisions in choosing implant contraception in the Dambalo Community Health Center Working Area. The study uses a quantitative approach with an observational analytical design and a cross-sectional design. The study sample consisted of 30 mothers of couples of childbearing age who were selected using purposive sampling techniques. The variables studied included age, education level, occupation, knowledge about contraception, and spousal support. Data were collected through questionnaires and family planning service registers, then analyzed univariately, bivariately, and multivariately using logistic regression. The results showed that there were no factors that had a statistically significant effect on mothers' decisions to choose implant contraception. However, the variables of education level and husband's support showed relatively high odds ratios, thus having clinical significance in contraceptive decision-making. The conclusion of this study indicates that mothers' decisions to choose implant contraception are influenced by the interaction of individual, social, and health service context factors. Therefore, a comprehensive, continuous, and needs- and preference-oriented family planning counseling approach is needed to increase the acceptance of implant contraception family planning midwifery